Peran Job Satisfaction Memediasi Pengaruh Work Engagement Terhadap Turnover Intention di Whiz Prime Hotel Kota Padang - Putri, Rahmi Hariyani; Abrian, Youmil; Surenda, Rian (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research is motivated by the fact that the turnover rate is relatively high. The purpose of this study was to determine whether there is an effect of Work engagement on Turnover Intention mediated by Job satisfaction at Whiz Prime Hotel at Padang. This research is causal associative research with a quantitative data approach, using a survey method. Employees at the Whiz Prime Hotel Padang who stayed there for more than a year make up the study's demographic. 41 participants made up the study's sample. The method of sampling is targeted sampling. Employees were given questionnaires including 41 statements, each of which had its validity and reliability examined. The method of data analysis employed in this investigation uses the Smart PLS 3.0 program. (1) There is a strong and favorable correlation between the job engagement and job satisfaction variables, according to the findings of data processing research using 41 samples that were tested for validity and reliability. (2) The impact of labor input on sales intent is negative and considerable at Whiz Prime Padang. (3) There is a negative and substantial relationship between factors measuring work satisfaction and quitting intention. (4) At Whiz Prime Hotel Padang, job satisfaction serves as a mediator between work input and sales intent, and this effect is negative and significant. According to the research, the hotel can improve employee job satisfaction and engagement in order to lower the likelihood of employee turnover in an organization. (5) It is suggested that the hotel encourage work engagement and job happiness to lessen occurrence of turnover intention in a firm because job satisfaction has the capacity to mediate elements affecting work engagement and turnover intention